Henry Winton Pfaff. (21st February 2020) - Boyd, Jack; Jarrett, Os; Murray, Max; Wright, Norman
Abstract : A much-loved small animal practitioner in Glasgow, he was a character and a real advocate for animals – it was he that brought contagious leukaemia in cats to the attention of researchers at the vet school.